Optimisation of High Frequency Seam Welding Parameters By Taguchi Method - Garg, Satish; Banwait, S. S.; Kumar, Ravneet (Asian Journal of Engineering and Applied Technology, 2013)
Seam welding is a versatile and most widely used method of fabrication in pipe and tube industries. A seam weld is a series of overlapping resistance spot welds made progressively along a joint by rotating circular electrodes. With the operating conditions becoming more and more stringent and the increased use of seam welded pipe joints in Industrial and domestic pipelines, the improvement in mechanical properties have become increasingly important. In this study, process parameters viz. Welding current, frequency of current, Roll Pressure and weld speed of Therma Tool welding machine were studied at three levels in a reputed company of Northern India by using L9(3)4 orthogonal arrays of Taguchi method to study tensile strength of electric resistance welding of pipes of 15 mm diameter of Class B. “Welding speed” was found to be contributing the most i.e. 45.43% in variation of Tensile strength followed by “roll pressure” which is contributing 22.93%. The parameter “Welding Current” contributing 20.92% and “Weld current frequency” is affecting least to variation being 10.58% of total variation of process. Lower levels of weld speed and Roll pressure, medium level of welding current and higher level of current frequency resulted in improvement in Tensile strength of pipes by 11.8%.